2018
DOI: 10.1021/acs.biochem.8b00361
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology of Trafficking Regulator of GLUT4 1 (TRARG1)

Abstract: Trafficking regulator of GLUT4 1 (TRARG1) was recently identified to localize to glucose transporter type 4 (GLUT4) storage vesicles (GSVs) and to positively regulate GLUT4 trafficking. Our knowledge of TRARG1 structure and membrane topology is limited to predictive models, hampering efforts to further our mechanistic understanding of how it carries out its functions. Here, we use a combination of bioinformatics prediction tools and biochemical assays to define the membrane topology of the 173-amino acid mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Cells were placed on ice, washed with cold PBS, and harvested in cold HES buffer (20 mM HEPES, 1 mM EDTA, and 250 mM sucrose (pH 7.4)) containing phosphatase and protease inhibitors. All subsequent steps were carried out at 4°C as described previously (67). Briefly, cells were homogenized using a Dounce tissue grinder prior to centrifugation at 500 ϫ g for 10 min.…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…Cells were placed on ice, washed with cold PBS, and harvested in cold HES buffer (20 mM HEPES, 1 mM EDTA, and 250 mM sucrose (pH 7.4)) containing phosphatase and protease inhibitors. All subsequent steps were carried out at 4°C as described previously (67). Briefly, cells were homogenized using a Dounce tissue grinder prior to centrifugation at 500 ϫ g for 10 min.…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…As part of our previous characterization of TRARG1 topology [26], we revealed that the Nterminal cytosolic domain of TRARG1 (1-100; del_101-173) does not exhibit reduced migration by SDS-PAGE, suggesting that this truncation mutant is not phosphorylated (Fig. S3A-B).…”
Section: Trarg1 Phosphorylation Regulates Its Interactome But Not Submentioning
confidence: 66%
“…1D for details of Ser/Thr/Tyr, Lys and Cys mutants used in this study). TRARG1 truncation mutants pcDNA3.1-HA-TRARG1-del_129-173-eGFP and pcDNA3.1-HA-TRARG1-del_101-173-eGFP were generated as previously described [26]. Residues 101-127 were deleted from pcDNA3.1-HA-TRARG1-eGFP to yield the plasmid pcDNA3.1-HA-TRARG1-del_101-127-eGFP, using overlap-extension site-directed mutagenesis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations